Family and the use and abuse of addictive potentials in young people - Castaño Castrillón, José Jaime; Páez Cala, Martha Luz (Informes Psicológicos, 2019)
This reflection article discusses in a broader way the results of a research carried out by the authors that sought to find the relationship between family variables and variables of addiction in university students, such as Internet addiction and the consumption of alcoholic beverages and psychoactive drugs. In the research, only a relationship was found with the presence of siblings and family typology, for Internet addiction. There was a broad search for references that, in general, confirm the relationship between family variables and addictive variables for Young students of secondary schools, but not for university students. As a result of this review, we hypothesize that, for young university students, family variables lose their importance in favor of other variables such as networks of friends, features of the young person at this stage of his or her development characterized by the search for autonomy and differentiation, and even residential independence from the family. Finally, this background course allows us to state that addictive behavior is determined by individual and contextual factors that require a complex systemic approach and a perspective focused on coping strategies and resilient capacity, as personal variables.
Keywords: consumption of alcoholic beverages; substances of oral abuse; family relations; students; internet